Modernizing the Divine Book. Translation strategies and language evolution in the Bible across English and Romanian - Andra-Iulia URSA (Swedish Journal of Romanian Studies)
This paper examines the translation and retranslation of the Bible in both English and Romanian, with a focus on the strategies used to adapt the sacred text for contemporary readers. By analysing two English versions, the New King James Version (1979) and the New English Translation (2001), alongside two Romanian versions, the Dumitru Cornilescu Version (1924/2014) and the Noua Traducere În Limba Română [the New Romanian translation] (2006), this study identifies linguistic shifts that reflect evolving reader comprehension. Using Andrew Chesterman’s translation strategies (1997), we compare syntactic, semantic, and pragmatic changes across different translations. Our corpus consists of 10 examples from Leviticus 19:2-13, which are analysed using a qualitative approach. Each translation and retranslation was marked with a number and noted to highlight the modification patterns. The findings reveal that language modernization, particularly in retranslation efforts, plays a key role in clarifying outdated vocabulary and making the text more accessible to modern readers. We conclude that these linguistic shifts are essential to bridging cultural and temporal gaps between ancient texts and contemporary audiences, ultimately showing that translation is not merely linguistic but also a reflection of changing social and cultural contexts.